Topological Attributes of Silicon Carbide SiC4-IIi,j Based on Ve-Degree and Ev-Degree - Abid Mahboob; Dalal Alrowaili; Sajid Mahboob Alam; Rifaqat Ali; Muhammad Waheed Rasheed; Imran Siddique (Journal of Chemistry)
The study of graphs containing edges and nodes is of great importance in science and in real life. Topological indices TIs are numerical parameters linked to chemical graphs used to estimate the biological, toxicological, and physical properties of chemical compounds. Recently, two terms, ev-degree- and ve-degree-based TIs, have been defined in chemical graph theory. In this paper, we have estimated degree-based TIs, namely, ev-degree Zagreb M type index, ev-degree Randic R index, ve-degree atom-bond connectivity ABC index, ve-degree geometric arithmetic index GA, ve-degree harmonic H index, and ve-degree sum-connectivity index for SiC4-IIi,j.